Electrolyte and electrochemical device including the same

By adding the compound of formula I and fluorocarboxylic acid ester to the electrolyte of the lithium-ion battery, the problem of insufficient storage and cycling performance of the lithium-ion battery at high temperatures is solved, and the kinetic performance of the electrolyte is improved and the cell performance is improved.

CN119812461AActive Publication Date: 2025-04-11NINGDE AMPEREX TECHNOLOGY LTD +1
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202510155215.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-12
Publication Date
2025-04-11
Estimated Expiration
2045-02-12

AI Technical Summary

Technical Problem

Existing lithium-ion batteries have shortcomings in storage performance and cycling performance at high temperatures, and their dynamic performance is low, making it difficult to meet the requirements of high temperature storage and cycling performance.

Method used

By adding the compound of formula I and fluorocarboxylic acid ester to the electrolyte, the mass content and ratio of the electrolyte are adjusted to improve the kinetic performance of the electrolyte and to improve the storage and cycling performance of the battery cell.

Benefits of technology

The kinetic performance of the electrolyte is improved, the high-temperature storage and cycling performance of the battery cell is improved, the impedance of the battery cell is reduced, and the negative impact of fluorocarboxylic acid ester on the interface components and kinetics is avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812461A_ABST
    Figure CN119812461A_ABST
Patent Text Reader

Abstract

The invention provides an electrolyte and an electrochemical device comprising the electrolyte, and the electrolyte comprises a compound shown as a formula I and fluorocarboxylic ester, in the formula, R1, R2, R3, R4 and R5 are respectively and independently selected from any one of fluorine atoms, trifluoromethyl, C1-C3 alkyl groups, cyano groups, nitryl groups, vinyl groups and ethynyl groups, and R1, R2, R3, R4 and R5 are respectively and independently selected from any one of fluorine atoms, trifluoromethyl, C1-C3 alkyl groups, cyano groups, nitryl groups, vinyl groups and ethynyl groups; based on the total mass of the electrolyte, the mass content of the compound shown in the formula I is A, the mass content of the fluoro-carboxylic ester is S, and A is larger than or equal to 0.01% and smaller than or equal to 5%; s satisfies 5% < = S < = 80%; a / S satisfies 0.001 < = A / S < = 1. According to the technical scheme provided by the invention, the dynamic performance of the electrolyte can be improved, and the storage and cycle performance of the battery cell can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of battery technology, in particular to the field of lithium-ion battery technology, and specifically to an electrolyte and an electrochemical device containing the electrolyte. Background Art

[0002] Electrochemical devices, especially lithium-ion batteries, are increasingly used in the field of portable electronic products. This is because electrochemical devices, especially lithium-ion batteries, have the advantages of high energy density, high operating voltage, light weight, low self-discharge rate, long cycle life, no memory effect, and environmental friendliness. In addition to smart electronic products (including mobile phones, notebooks, cameras, etc.) and energy storage products, there is an increasing demand for higher-power electronic products such as electric vehicles, power tools, drones, electric ships, etc. At the same time, the requirements for high-temperature gas production and safety performance of electrochemical devices are also getting higher and higher. Therefore, it is particularly important to develop electrochemical devices, especially lithium-ion batteries, with relatively low impedance and high-temperature storage and cycle performance. Summary of the invention

[0003] The purpose of the present application is to provide an electrolyte and an electrochemical device containing the electrolyte to improve the storage and cycle performance of the battery cell. The specific scheme is as follows:

[0004] According to the first aspect of the present application, the present application provides an electrolyte, the electrolyte comprising: a compound of formula I and a fluorocarboxylic acid ester;

[0005]

[0006] Among them, R 1 , R 2 , R 3 , R 4 and R 5 Each is independently selected from any one of a fluorine atom, a trifluoromethyl group, a C1-C3 alkyl group, a cyano group, a nitro group, a vinyl group, and an acetylene group; based on the total mass of the electrolyte, the mass content of the compound of formula I is A, and the mass content of the fluorocarboxylic acid ester is S, wherein A satisfies: 0.01%≤A≤5%; S satisfies: 5%≤S≤80%; and A / S satisfies: 0.001≤A / S≤1.

[0007] The use of fluorocarboxylic acid esters as solvents in electrolytes can further improve the oxidation resistance of electrolytes at the positive electrode interface and improve the stability of electrolytes at the interface. However, fluorocarboxylic acid esters have the defect of significantly reducing the dynamics of electrolytes. Based on this, the present application has found through research that the introduction of the compound of formula I into the electrolyte added with fluorocarboxylic acid esters can further improve the dynamics of the electrolyte, thereby improving the storage and cycle performance of the battery cell. By introducing the compound of formula I into the electrolyte added with fluorocarboxylic acid esters, on the one hand, due to the structural characteristics of the compound of formula I itself, such as pyridine and sulfonate structures, they can participate in the solvation of lithium ions in the electrolyte, thereby improving the dynamics of the electrolyte; on the other hand, the compound of formula I migrates to the positive and negative electrode interfaces through solvation to participate in the redox reaction to generate interface components rich in sulfur, fluorine and nitrogen structures, thereby improving the storage and cycle performance of the battery cell. At the same time, the present application has found through research that the addition of nitrogen heterocyclic substances and sulfonic acid-containing or sulfur-containing substances separately will cause adverse effects on the negative electrode interface, and the impedance is also relatively large. The addition of the compound of formula I provided by the present application does not deteriorate the impedance, and the storage performance improvement effect is also good. At the same time, compared with the substances containing N heterocyclic structures disclosed in the prior art, the lone pair of electrons in the nitrogen atom of the pyridine structure of the compound of formula I provided by the present application can be complexed with transition metal elements, can be preferentially adsorbed on the positive electrode interface, and promote the film-forming reaction of the sulfonate structure at the positive electrode interface. In addition, the structure of the pyridine conjugated ring can form π-π conjugation with the large π bond of graphite, thereby promoting the reduction and decomposition of the sulfonate at the negative electrode interface to form a negative electrode protective film. In addition, the decomposition products of pyridine and sulfonate have high heat resistance, which can significantly improve the performance of the battery at high temperature. At the same time, the stable interface components formed by them can improve the battery cycle performance. In addition, the present application has found in the research that the addition amount of the compound of formula I and the fluorocarboxylic acid ester will also greatly affect the improvement of the corresponding performance. For example, excessive addition of the compound of formula I will lead to impedance deterioration, and excessive addition of the fluorocarboxylic acid ester will lead to a negative impact on the electrolyte dynamics. Further adjusting the dosage relationship of the compound of formula I and the fluorocarboxylic acid ester within the above range can further improve the kinetic performance of the electrolyte and achieve better improvement in battery cell storage and cycle performance.

[0008] In some embodiments of the present application, the mass content A of the compound of formula I in the electrolyte satisfies: 0.05%≤A≤5%. By further adjusting the mass content A of the compound of formula I in the electrolyte within the above range, the defect of increased impedance caused by excessive participation of the compound of formula I in film formation can be reduced, thereby achieving further improvement in battery cell storage, impedance and cycle performance.

[0009] In some embodiments of the present application, the ratio A / S of the mass content A of the compound of formula I in the electrolyte to the mass content S of the fluorocarboxylic acid ester in the electrolyte satisfies: 0.001≤A / S≤0.5; preferably, A / S satisfies: 0.001≤A / S≤0.1. By further adjusting the dosage relationship of the compound of formula I and the fluorocarboxylic acid ester within the above range, the deterioration of storage performance at high temperature caused by excessive compound of formula I and the negative impact of fluorocarboxylic acid ester on interface components and dynamics can be further reduced, so as to better improve the kinetic performance of the electrolyte and the storage and cycle performance of the battery cell.

[0010] In some embodiments of the present application, the mass content S of the fluorocarboxylic acid ester in the electrolyte satisfies: 10%≤S≤50%. By further adjusting the mass content S of the fluorocarboxylic acid ester in the electrolyte within the above range, the kinetic performance of the electrolyte and the storage and cycle performance of the battery cell can be further improved. For example, when the amount of the fluorocarboxylic acid ester is lower than the above range, the storage improvement effect is not obvious enough. When the amount of the fluorocarboxylic acid ester is higher than the above range, the kinetics of the electrolyte will decrease significantly, resulting in an increase in the impedance of the battery cell, further affecting the improvement effect of the corresponding performance.

[0011] In some embodiments of the present application, the compound of formula I includes at least one of the compounds represented by formula I-1 to formula I-12:

[0012]

[0013] In the technical solution provided in the present application, when the compound of formula I selects at least one of the above compounds, the kinetic performance of the electrolyte and the storage and cycle performance improvement effects of the battery cell can be further improved.

[0014] In some embodiments of the present application, the fluorocarboxylate comprises at least one of the compounds represented by Formula 1 to Formula 8:

[0015]

[0016] In the technical solution provided in the present application, when the fluorocarboxylic acid ester is selected from at least one of the above-mentioned compounds, the kinetic performance of the electrolyte and the storage and cycle performance of the battery cell can be further improved.

[0017] In some embodiments of the present application, the electrolyte further includes a carbonate compound, and the carbonate compound includes at least one of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, ethylene carbonate, and propylene carbonate. As described above, the use of fluorocarboxylic acid esters in the electrolyte will reduce the kinetics of the electrolyte to a certain extent, and the present application has found through research that further introducing carbonate compounds into the electrolyte added with fluorocarboxylic acid esters can improve the dissociation of lithium salts and further improve the kinetics of the electrolyte. Since carbonate compounds participate in redox reactions, there is a serious problem of gas production, especially under high voltage, but when they are combined with the compound of formula I, the compound of formula I can significantly improve the interface stability, thereby reducing the oxidative decomposition of carbonate compounds and reducing the deterioration of high temperature performance.

[0018] In some embodiments of the present application, the electrolyte further includes a carbonate compound, and based on the total mass of the electrolyte, the mass content of the carbonate compound in the electrolyte is C, and C satisfies: 10%≤C≤30%. Further regulating the mass content C of the carbonate compound in the electrolyte within the above range can further improve the kinetic performance of the electrolyte and the storage and cycle performance of the battery cell.

[0019] In some embodiments of the present application, the ratio C / A of the mass content C of the carbonate compound in the electrolyte to the mass content A of the compound of formula I in the electrolyte satisfies the following relationship: 20≤C / A≤120. Further limiting the ratio C / A of the mass content C of the carbonate compound in the electrolyte to the mass content A of the compound of formula I in the electrolyte within the above range can reduce the excessive decomposition of the carbonate compound on the interface that affects the film-forming effect of the compound of formula I, and further improve the storage performance.

[0020] In some embodiments of the present application, the ratio C / S of the mass content C of the carbonate compound in the electrolyte to the mass content S of the fluorocarboxylic acid ester in the electrolyte satisfies the following relationship: 0.15≤C / S≤5. Further regulating the ratio C / S of the mass content C of the carbonate compound in the electrolyte to the mass content S of the fluorocarboxylic acid ester in the electrolyte within the above range can ensure that the electrolyte has sufficient dynamics and further stabilize the cycle performance.

[0021] According to the second aspect of the present application, the present application further provides an electrochemical device, the electrochemical device comprising the electrolyte described in any one of the first aspects of the present application. The electrochemical device comprising the above electrolyte has relatively low impedance and good high temperature storage and cycle performance. DETAILED DESCRIPTION

[0022] The technical solution of the present application is further described below through specific embodiments, which do not limit the protection scope of the present application. Some non-essential modifications and adjustments made by others based on the concept of the present application still fall within the protection scope of the present application.

[0023] It should be noted that in the following content, lithium-ion batteries are used as an example of secondary batteries to explain the present application, but the secondary batteries of the present application are not limited to lithium-ion batteries, but can also be any other suitable secondary batteries, such as lithium metal secondary batteries, lithium polymer secondary batteries or lithium ion polymer secondary batteries, etc.

[0024] 1. Electrolyte

[0025] According to the first aspect of the present application, the present application provides an electrolyte, the electrolyte comprising: a compound of formula I and a fluorocarboxylic acid ester;

[0026]

[0027] Among them, R 1 , R 2 , R 3 , R 4 and R 5 Each is independently selected from any one of a fluorine atom, a trifluoromethyl group, a C1-C3 alkyl group, a cyano group, a nitro group, a vinyl group, and an acetylene group; based on the total mass of the electrolyte, the mass content of the compound of formula I is A, and the mass content of the fluorocarboxylic acid ester is S, wherein A satisfies: 0.01%≤A≤5%; S satisfies: 5%≤S≤80%; and A / S satisfies: 0.001≤A / S≤1.

[0028] Specifically, the chemical formula of the "fluorine atom" is -F. The "trifluoromethyl" is a group formed by covalently bonding a carbon atom (C) and three fluorine atoms (F), and its chemical formula is -CF 3 The "C1-C3 alkyl" refers to a hydrocarbon group formed by removing a hydrogen atom from an alkane molecule with 1 to 3 carbon atoms, usually represented by "-R", also known as an R group. The "cyano" refers to a group in which a carbon atom and a nitrogen atom are connected by a triple bond, with the chemical formula -CN. The "nitro" refers to the group remaining after removing a hydroxyl group from a nitric acid molecule, with the chemical formula -NO 2 The "vinyl" is obtained by removing a hydrogen atom from an ethylene molecule, and its chemical formula is -HC=CH 2 The "ethynyl group" is equivalent to a group formed by removing a hydrogen atom from an acetylene molecule, and its chemical formula is CH≡C-. Specifically, the "fluorocarboxylate" is a type of carboxylate compound containing fluorine atoms, and its chemical formula is CnF2n+1COOR.

[0029] Specifically, in some embodiments of the present application, based on the total mass of the electrolyte, the mass content A of the compound of formula I can be 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4. %, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4.0%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5.0% or a range consisting of any two of the above values. Specifically, in some embodiments of the present application, based on the total mass of the electrolyte, the mass content S of the fluorocarboxylic acid ester can be 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80%, or a range consisting of any two of the above values. Specifically, in some embodiments of the present application, based on the total mass of the electrolyte, the ratio A / S of the mass content A of the compound of formula I to the mass content S of the fluorocarboxylic acid ester can be 0.001, 0.002, 0.003, 0.004, 0.005, 0.006, 0.007, 0.008, 0.009, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0 or a range consisting of any two of the above values.

[0030] The use of fluorocarboxylic acid esters as solvents in electrolytes can further improve the oxidation resistance of electrolytes at the positive electrode interface and improve the stability of electrolytes at the interface. However, fluorocarboxylic acid esters have the defect of significantly reducing the dynamics of electrolytes. Based on this, the present application has found through research that the introduction of the compound of formula I into the electrolyte added with fluorocarboxylic acid esters can further improve the dynamics of the electrolyte, thereby improving the storage and cycle performance of the battery cell. By introducing the compound of formula I into the electrolyte added with fluorocarboxylic acid esters, on the one hand, due to the structural characteristics of the compound of formula I itself, such as pyridine and sulfonate structures, they can participate in the solvation of lithium ions in the electrolyte, thereby improving the dynamics of the electrolyte; on the other hand, the compound of formula I migrates to the positive and negative electrode interfaces through solvation to participate in the redox reaction to generate interface components rich in sulfur, fluorine and nitrogen structures, thereby improving the storage and cycle performance of the battery cell. At the same time, the present application has found through research that the addition of nitrogen heterocyclic substances and sulfonic acid-containing or sulfur-containing substances separately will cause adverse effects on the negative electrode interface, and the impedance is also relatively large. The addition of the compound of formula I provided by the present application does not deteriorate the impedance, and the storage performance improvement effect is also good. At the same time, compared with the substances containing N heterocyclic structures disclosed in the prior art, the lone pair of electrons in the nitrogen atom of the pyridine structure of the compound of formula I provided by the present application can be complexed with transition metal elements, can be preferentially adsorbed on the positive electrode interface, and promote the film-forming reaction of the sulfonate structure at the positive electrode interface. In addition, the structure of the pyridine conjugated ring can form π-π conjugation with the large π bond of graphite, thereby promoting the reduction and decomposition of the sulfonate at the negative electrode interface to form a negative electrode protective film. In addition, the decomposition products of pyridine and sulfonate have high heat resistance, which can significantly improve the performance of the battery at high temperature. At the same time, the stable interface components formed by them can improve the battery cycle performance. In addition, the present application has found in the research that the addition amount of the compound of formula I and the fluorocarboxylic acid ester will also greatly affect the improvement of the corresponding performance. For example, excessive addition of the compound of formula I will lead to impedance deterioration, and excessive addition of the fluorocarboxylic acid ester will lead to a negative impact on the dynamics of the electrolyte. Further regulating the dosage relationship of the compound of formula I and the fluorocarboxylic acid ester within the above range can further improve the kinetic performance of the electrolyte and achieve better improvement in battery cell storage and cycle performance.

[0031] In some embodiments of the present application, the mass content A of the compound of formula I in the electrolyte satisfies: 0.05%≤A≤5%; preferably, the mass content A of the compound of formula I in the electrolyte satisfies: 0.1%≤A≤5%; preferably, the mass content A of the compound of formula I in the electrolyte satisfies: 0.2%≤A≤5%; more preferably, the mass content A of the compound of formula I in the electrolyte satisfies: 0.5%≤A≤5%. By further adjusting the range of the mass content A of the compound of formula I in the electrolyte, the defect of increased impedance caused by excessive participation of the compound of formula I in film formation can be further reduced, thereby achieving further improvement in battery cell storage, impedance and cycle performance.

[0032] In some embodiments of the present application, the ratio A / S of the mass content A of the compound of formula I in the electrolyte to the mass content S of the fluorocarboxylate in the electrolyte satisfies: 0.001≤A / S≤0.5; in some embodiments of the present application, the ratio A / S of the mass content A of the compound of formula I in the electrolyte to the mass content S of the fluorocarboxylate in the electrolyte satisfies: 0.001≤A / S≤0.1. By further adjusting the dosage relationship of the compound of formula I and the fluorocarboxylate within the above range, the deterioration of storage performance at high temperature caused by excessive compound of formula I and the negative impact of fluorocarboxylate on interface components and dynamics can be reduced, so as to further improve the kinetic performance of the electrolyte and the storage and cycle performance of the battery cell.

[0033] In some embodiments of the present application, the mass content S of the fluorocarboxylic acid ester in the electrolyte satisfies: 10%≤S≤50%. By further adjusting the mass content S of the fluorocarboxylic acid ester in the electrolyte within the above range, the kinetic performance of the electrolyte and the storage and cycle performance of the battery cell can be further improved. For example, when the amount of the fluorocarboxylic acid ester is lower than the above range, the storage improvement effect is not obvious enough. When the amount of the fluorocarboxylic acid ester is higher than the above range, the kinetics of the electrolyte will decrease significantly, resulting in an increase in the impedance of the battery cell, further affecting the improvement effect of the corresponding performance.

[0034] In some embodiments of the present application, the compound of formula I includes at least one of the compounds represented by formula I-1 to formula I-12:

[0035]

[0036] In the technical solution provided in the present application, when the compound of formula I selects at least one of the above compounds, the kinetic performance of the electrolyte and the storage and cycle performance improvement effects of the battery cell can be further improved.

[0037] In some embodiments of the present application, the fluorocarboxylate comprises at least one of the compounds represented by Formula 1 to Formula 8:

[0038]

[0039] In the technical solution provided in the present application, when the fluorocarboxylic acid ester is selected from at least one of the above-mentioned compounds, the kinetic performance of the electrolyte and the storage and cycle performance of the battery cell can be further improved.

[0040] In some embodiments of the present application, the electrolyte further includes a carbonate compound, and the carbonate compound includes at least one of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, ethylene carbonate, and propylene carbonate. As described above, the use of fluorocarboxylic acid esters in the electrolyte will reduce the kinetics of the electrolyte to a certain extent, and the present application has found through research that further introducing carbonate compounds into the electrolyte added with fluorocarboxylic acid esters can improve the dissociation of lithium salts and further improve the kinetics of the electrolyte. Since carbonate compounds participate in redox reactions, there is a serious problem of gas production, especially under high voltage, but when they are combined with the compound of formula I, the compound of formula I can significantly improve the interface stability, thereby reducing the oxidative decomposition of carbonate compounds and reducing the deterioration of high temperature performance.

[0041] In some embodiments of the present application, the electrolyte further includes a carbonate compound, and based on the total mass of the electrolyte, the mass content of the carbonate compound is C, and C satisfies: 10%≤C≤30%. Specifically, in some embodiments of the present application, based on the total mass of the electrolyte, the mass content C of the carbonate compound can be 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30% or a range consisting of any two of the above values. Further regulating the mass content C of the carbonate compound in the electrolyte within the above range can further improve the kinetic performance of the electrolyte and the storage and cycle performance of the battery cell.

[0042] In some embodiments of the present application, the ratio C / A of the mass content C of the carbonate compound in the electrolyte to the mass content A of the compound of formula I in the electrolyte satisfies the following relationship: 20≤C / A≤120. Specifically, in some embodiments of the present application, the ratio C / A of the mass content C of the carbonate compound in the electrolyte to the mass content A of the compound of formula I in the electrolyte may be 20, 21, 22, 23, 24, 25%, 26, 27, 28, 29, 30%, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47%, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85 109, 110, 111, 112, 113, 114, 115, 116, 117, 118, 119, 120, or a range consisting of any two of the above values. Further limiting the ratio C / A of the mass content C of the carbonate compound in the electrolyte to the mass content A of the compound of formula I in the electrolyte within the above range can reduce the excessive decomposition of the carbonate compound on the interface that affects the film-forming effect of the compound of formula I, and further improve the storage performance.

[0043] In some embodiments of the present application, the ratio C / S of the mass content C of the carbonate compound in the electrolyte to the mass content S of the fluorocarboxylic acid ester in the electrolyte satisfies the following relationship: 0.15≤C / S≤5. Specifically, in some embodiments of the present application, the ratio C / S of the mass content C of the carbonate compound in the electrolyte to the mass content S of the fluorocarboxylic acid ester in the electrolyte can be 0.15, 0.16, 0.17, 0.18, 0.19, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.1 .7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0 or a range consisting of any two of the above values. Further, the ratio C / S of the mass content C of the carbonate compound in the electrolyte to the mass content S of the fluorocarboxylic acid ester in the electrolyte is regulated within the above range to ensure that the electrolyte has sufficient dynamics and further stabilize the cycle performance.

[0044] In some embodiments of the present application, the electrolyte provided by the present application may further include some other components, which may include but are not limited to: diethyl carbonate (DEC), ethyl methyl carbonate (EMC) or dimethyl carbonate (DMC). In some embodiments of the present application, the other components may include ether solvents, which may include but are not limited to: at least one of 1,3-dioxolane (DOL) and ethylene glycol dimethyl ether (DME).

[0045] In some embodiments of the present application, the electrolyte provided in the present application may also include a lithium salt as an electrolyte. The lithium salt in the electrolyte includes but is not limited to: LiClO 4 、LiAsF 6 、LiPF 6 、LiSbF 6 、LiSO 3 F、LiN(FSO 2 ) 2 、LiCF 3 SO 3 、LiN(FSO 2 )(CF 3 SO 2 )、LiN(CF 3 SO 2 ) 2 、LiN(C 2 F5 SO 2 ) 2 , lithium bis(oxalate)borate, lithium tri(oxalate)phosphate, lithium difluorobis(oxalate)phosphate or lithium tetrafluoro(oxalate)phosphate. In addition, the above lithium salts can be used alone or in combination of two or more. In some embodiments, the lithium salt includes LiPF 6 In some embodiments, based on the total mass of the electrolyte, the mass content of the lithium salt in the electrolyte is 10% to 20%. Specifically, based on the total mass of the electrolyte, the mass content of the lithium salt in the electrolyte is 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, or a range consisting of any two of the above values.

[0046] In some embodiments of the present application, the preparation method of the electrolyte provided in the present application is not limited, and can be prepared in the manner of a conventional electrolyte. In some embodiments, the electrolyte of the present application can be prepared by mixing the components.

[0047] 2. Electrochemical Device

[0048] According to the second aspect of the present application, the present application further provides an electrochemical device, the electrochemical device comprising the electrolyte described in any one of the first aspects of the present application. The electrochemical device comprising the above electrolyte has relatively low impedance and good high temperature storage and cycle performance.

[0049] In some embodiments of the present application, the electrochemical device of the present application includes, but is not limited to: all kinds of primary batteries, secondary batteries, fuel cells, solar cells or capacitors. In some embodiments of the present application, the electrochemical device is a lithium secondary battery. In some embodiments of the present invention, the lithium secondary battery includes, but is not limited to: lithium metal secondary battery, lithium ion secondary battery, lithium polymer secondary battery or lithium ion polymer secondary battery.

[0050] In some embodiments of the present application, the electrochemical device of the present application may also be a negative electrode-free battery system.

[0051] 1. Negative electrode

[0052] In some embodiments of the present application, the electrochemical device further comprises a negative electrode, the negative electrode comprising a negative electrode current collector and a negative electrode material layer located on at least one surface of the negative electrode current collector, the negative electrode active material layer comprising a negative electrode active material, and the negative electrode active material is any material that can electrochemically absorb and release metal ions such as lithium ions. In some embodiments of the present application, the negative electrode active material comprises a carbonaceous material (graphite), a silicon material, a hard carbon material or a lithium metal material. In some embodiments of the present application, the negative electrode active material comprises one or more of the above.

[0053] In some embodiments of the present application, the structure of the negative electrode may be a negative electrode structure known in the art that can be used in an electrochemical device.

[0054] In some embodiments of the present application, the preparation method of the negative electrode is a preparation method of the negative electrode that can be used for an electrochemical device that is well known in the art. Exemplarily, the negative electrode can be obtained by the following method: mixing the negative electrode active material, the conductive agent, and the binder in a solvent, and heating the thickener as needed to prepare a negative electrode active material slurry, and coating the negative electrode active material slurry on the negative electrode current collector, drying, and cold pressing to form a negative electrode active material layer. In some embodiments, the solvent may include, but is not limited to, water, N-methylpyrrolidone.

[0055] 2. Positive electrode

[0056] In some embodiments of the present application, the electrochemical device further comprises a positive electrode, the positive electrode comprising a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector. The specific types of positive electrode active materials of the positive electrode active material layer are not subject to specific restrictions and can be selected according to needs. In some embodiments of the present application, the positive electrode active material comprises a lithium transition metal composite oxide. In some embodiments, the positive electrode active material is selected from at least one of the following: lithium cobalt oxide, lithium nickel manganese cobalt ternary material, lithium manganese oxide, lithium nickel manganese oxide or lithium iron phosphate.

[0057] In some embodiments of the present application, the structure of the positive electrode is a positive electrode structure that is well known in the art and can be used in a secondary battery.

[0058] In some embodiments of the present application, the preparation method of the positive electrode is a preparation method of the positive electrode that can be used for a secondary battery and is well known in the art. For example, the positive electrode can be obtained by the following method: a positive electrode active material, a conductive agent, and a binder are mixed in a solvent to prepare a positive electrode active material slurry, and the positive electrode active material slurry is coated on a positive electrode current collector, dried, and cold pressed to form a positive electrode active material layer. In some embodiments, the solvent may include water, N-methylpyrrolidone, etc., but is not limited thereto.

[0059] 3. Isolation film

[0060] In some embodiments of the present application, the electrochemical device further comprises an isolating membrane, which is used to prevent short circuits. The material and shape of the isolating membrane are not particularly limited, and it may be any technology disclosed in the prior art. For example, in some embodiments, the isolating membrane comprises a substrate layer, which is a non-woven fabric, a film or a composite film having a porous structure, and the material of the substrate layer may be selected from at least one of polyethylene, polypropylene, polyethylene terephthalate and polyimide. Specifically, the material of the substrate layer may be selected from at least one of a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film. A surface treatment layer is provided on at least one surface of the substrate layer. The surface treatment layer may be a polymer layer, an inorganic layer or a layer formed by a mixed polymer and an inorganic substance. Specifically, the inorganic layer includes inorganic particles and a binder, the inorganic particles can be selected from one or a combination of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate, and the binder can be selected from one or a combination of polyvinylidene fluoride, a polymer of vinylidene fluoride-hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene and polyhexafluoropropylene.

[0061] 3. Electronic equipment

[0062] The electrolyte according to the present application can enable the electrochemical device to have relatively low impedance and good high-temperature storage and cycle performance, so that the electrochemical device manufactured thereby is suitable for electronic devices in various fields.

[0063] The use of the electrochemical device of the present application is not particularly limited, and it can be used for any use known in the prior art. In one embodiment, the electrochemical device of the present application can be used for, but not limited to: laptop computers, pen-input computers, mobile computers, e-book players, portable phones, portable fax machines, portable copiers, portable printers, head-mounted stereo headphones, video recorders, LCD TVs, portable cleaners, portable CD players, mini-discs, transceivers, electronic notepads, calculators, memory cards, portable recorders, radios, backup power supplies, motors, cars, motorcycles, power-assisted bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, large household batteries and lithium-ion capacitors, etc. In addition, the electrochemical device provided in the present application is applicable to energy storage power stations, marine vehicles, and air vehicles in addition to the electronic equipment listed above. The air vehicle includes an air vehicle in the atmosphere and an air vehicle outside the atmosphere.

[0064] Example

[0065] Hereinafter, the present application will be described in more detail by using specific examples and comparative examples.

[0066] The test methods used in the following examples and comparative examples are as follows:

[0067] (1) Lithium-ion battery DC resistance DCR test

[0068] Place the lithium-ion battery in a constant temperature environment of 0℃ and let it stand for 5 minutes to allow the lithium-ion battery to reach a constant temperature. Record the lithium-ion battery voltage at this time as U1. Discharge at a constant current of 0.1C for 10 minutes and record the lithium-ion battery voltage at this time as U2. The impedance of the lithium-ion battery at 0℃ is DCR = (U1-U2) / 0.1C.

[0069] (2) High temperature gas production performance test of lithium-ion batteries

[0070] Place the lithium-ion battery in a 25°C constant temperature environment and let it stand for 30 minutes to allow the lithium-ion battery to reach a constant temperature of 25°C. Charge it to 4.3V at a constant current of 0.5C, and charge it to a current of 0.025C at a constant voltage of 4.3V. Record the thickness of the lithium-ion battery at this time as the initial thickness H0. Transfer the lithium-ion battery to a 60°C constant temperature box and store it for 30 days. During this period, test and record the thickness of the lithium-ion battery every 6 days. The test thickness recorded after 30 days is the storage thickness H1. High temperature storage thickness expansion rate = (H1-H0) / H0×100%.

[0071] (3) Lithium-ion battery cycle performance test

[0072] Place the lithium-ion battery in a 25°C constant temperature environment and let it stand for 30 minutes to allow the lithium-ion battery to reach a constant temperature of 25°C. Charge to 4.3V at a constant current of 0.5C, charge to a current of 0.025C at a constant voltage of 4.3V, let it stand for 5 minutes, discharge to 2.8V at a constant current of 0.5C, record the initial discharge capacity as C0, cycle 500 times with the above charge and discharge steps, and record the discharge capacity after 150 cycles as C1. Cycle capacity retention rate = C1 / C0×100%.

[0073] Example 1-1

[0074] (1) Preparation of positive electrode

[0075] The positive electrode active material NCM811, the conductive agent Super P, and the binder polyvinylidene fluoride are mixed in a weight ratio of 97:1.4:1.6, added into N-methylpyrrolidone (NMP) solvent, and stirred evenly under the action of a vacuum mixer to obtain a positive electrode slurry, wherein the solid content of the positive electrode slurry is 72wt%; the positive electrode slurry is evenly coated on the positive electrode current collector aluminum foil; the coated aluminum foil is dried at 85°C, and then after cold pressing, cutting and slitting, it is dried under vacuum conditions at 85°C for 4h to obtain a positive electrode.

[0076] (2) Preparation of negative electrode

[0077] The negative electrode active material artificial graphite, conductive agent Super P, thickener sodium carboxymethyl cellulose (CMC), and binder styrene butadiene rubber (SBR) were mixed in a weight ratio of 96:2:0.8:1.2, and deionized water was added to obtain a negative electrode slurry under the action of a vacuum mixer, wherein the solid content of the negative electrode slurry was 54wt%; the negative electrode slurry was stirred at a negative electrode active material area density of 7.8mg / cm 2 The negative electrode is evenly coated on the negative electrode current collector copper foil; the coated copper foil is dried at 85°C, and then cold pressed, cut and slit, and then dried at 120°C under vacuum conditions for 12 hours to obtain the negative electrode.

[0078] (3) Preparation of electrolyte

[0079] In a dry (water content <10 ppm) argon atmosphere glove box, the solvents were mixed in a mass ratio of EC:DEC:EMC=30:40:30, and then fully dried lithium salt LiPF 6 (1 mol / kg, referred to as 1M), after dissolving and fully stirring, add the compound of formula I (Formula I-1) and the fluorocarboxylic acid ester (Formula 1), mix evenly to obtain an electrolyte; wherein, based on the total mass of the electrolyte, the mass content of the compound of formula I (Formula I-1) is 0.1wt%, the mass content of the fluorocarboxylic acid ester (Formula 1) is 5wt%, and LiPF 6 The mass content is 12.5wt%.

[0080] (4) Preparation of isolation membrane

[0081] A 9 μm thick polyethylene (PE) isolation membrane was selected, and PVDF slurry, inorganic particles (flaky boehmite and Al 2 O 3 The final isolation membrane was obtained after the slurry was coated and dried with a mass ratio of 70:30, the coating thickness was 3um, and the membrane porosity was 55%.

[0082] (5) Preparation of lithium-ion batteries

[0083] The positive electrode, the separator, and the negative electrode are stacked in order, so that the separator is between the positive and negative electrodes to play an isolating role, and then they are wound to obtain a bare cell; after welding the pole ears, the bare cell is placed in an outer packaging foil aluminum-plastic film, and the prepared electrolyte is injected, and then vacuum packaging, standing, formation (0.02C constant current charging to 3.3V, and then 0.1C constant current charging to 3.8V), shaping, capacity testing and other processes are carried out to obtain a soft-pack lithium-ion battery.

[0084] Example 1-2 to Example 1-26

[0085] Except for adjusting the specific types and mass content parameters of the compound of formula I and the fluorocarboxylic acid ester according to Table 1, the other parameters of Examples 1-2 to 1-26 are the same as those of Example 1-1.

[0086] Comparative Example 1-1 to Comparative Example 1-17

[0087] Except for adjusting the specific types and mass content parameters of the compound of formula I and the fluorocarboxylic acid ester according to Table 1, the other parameters of Comparative Examples 1-1 to Comparative Examples 1-17 are the same as those of Example 1-1.

[0088] According to the above test method, the impedance DCR (mΩ), high temperature storage thickness expansion rate (%), and cycle capacity retention rate (%) of the lithium ion batteries prepared by Examples 1-1 to 1-26 and Comparative Examples 1-1 to 1-17 were tested respectively, and the results are shown in Table 1:

[0089] Table 1

[0090]

[0091]

[0092] According to the results presented in Table 1, by adding the compound of formula I and the fluorocarboxylic acid ester to the electrolyte at the same time, the cycle performance of the lithium-ion battery can be significantly improved, and by further adjusting the amount of the compound of formula I and the fluorocarboxylic acid ester in the electrolyte, the impedance and high-temperature storage performance of the lithium-ion battery can be further improved.

[0093] Example 2-1 to Example 2-12

[0094] Based on the results in Table 1, the corresponding examples further explore the effects of other components and amounts on the impedance, high temperature storage, and cycle performance of lithium-ion batteries. In addition to adjusting the specific type and mass content of the carbonate compound and the mass content of the compound of Formula I according to Table 2, the remaining parameters of Examples 2-1 to 2-12 are the same as those of Examples 1-13.

[0095] The impedance DCR (mΩ), high temperature storage thickness expansion rate (%) and cycle capacity retention rate (%) of the lithium ion batteries prepared by Examples 2-1 to 2-12 were tested according to the above test methods, and the results are shown in Table 2:

[0096] Table 2

[0097]

[0098]

[0099] The results shown in Table 2 indicate that the impedance performance, high temperature storage, and cycle performance of lithium-ion batteries can be further improved by further adding carbonate compounds to the electrolyte.

[0100] It is to be understood that the present application is described by some embodiments, and it is known to those skilled in the art that various changes or equivalent substitutions may be made to these features and embodiments without departing from the scope of the present application. In addition, under the teachings of the present application, these features and embodiments may be modified to adapt to specific circumstances and materials without departing from the scope of the present application. Therefore, the present application is not limited by the specific embodiments disclosed herein, and all embodiments falling within the scope of the claims of the present application are within the scope protected by the present application.

Claims

1. An electrolyte, wherein The electrolyte comprises: a compound of formula I and a fluorocarboxylic acid ester; Among them, R 1 , R 2 , R 3 , R 4 and R 5 Each is independently selected from any one of a fluorine atom, a trifluoromethyl group, a C1-C3 alkyl group, a cyano group, a nitro group, a vinyl group, and an acetylene group; based on the total mass of the electrolyte, the mass content of the compound of formula I is A, and the mass content of the fluorocarboxylic acid ester is S, wherein A satisfies: 0.01%≤A≤5%; S satisfies: 5%≤S≤80%; and A / S satisfies: 0.001≤A / S≤1.

2. The electrolyte according to claim 1, wherein The mass content A of the compound of formula I in the electrolyte satisfies: 0.05%≤A≤5%.

3. The electrolyte according to claim 1, wherein The ratio A / S of the mass content A of the compound of formula I in the electrolyte to the mass content S of the fluorocarboxylic acid ester in the electrolyte satisfies: 0.001≤A / S≤0.5; preferably, A / S satisfies: 0.001≤A / S≤0.

1.

4. The electrolyte according to claim 1, wherein The mass content S of the fluorocarboxylic acid ester in the electrolyte satisfies: 10%≤S≤50%.

5. The electrolyte according to claim 1, wherein The compound of formula I includes at least one of the compounds represented by formula I-1 to formula I-12:

6. The electrolyte according to claim 1, wherein The fluorocarboxylate comprises at least one of the compounds represented by Formula 1 to Formula 8:

7. The electrolyte according to claim 1, wherein The electrolyte further comprises a carbonate compound. Based on the total mass of the electrolyte, the mass content of the carbonate compound is C, and C satisfies: 10%≤C≤30%.

8. The electrolyte according to claim 7, characterized in that The ratio C / A of the mass content C of the carbonate compound in the electrolyte to the mass content A of the compound of formula I in the electrolyte satisfies the following relationship: 20≤C / A≤120.

9. The electrolyte according to claim 7, characterized in that The ratio C / S of the mass content C of the carbonate compound in the electrolyte to the mass content S of the fluorocarboxylic acid ester in the electrolyte satisfies the following relationship: 0.15≤C / S≤5. 10 . An electrochemical device comprising the electrolyte according to claim 1 .

Citation Information

Patent Citations

  • Battery electrolyte additive and electrolyte giving consideration to high and low temperature properties as well as nickelic ternary lithium ion battery

    CN109755635A

  • Fluorine-containing sulfonate electrolyte additive, electrolyte containing additive and lithium ion battery

    CN112054241A

  • High-low temperature lithium ion battery electrolyte and lithium ion battery

    CN112310473A

  • Battery electrolyte and preparation method of benzenesulfonate compound in battery electrolyte

    CN113851711A

  • Lithium ion battery electrolyte, lithium ion battery and method for improving battery performance

    CN115863760A